b - Morrison, Toni. (b, 2019)
A vital new non-fiction collection from one of the most celebrated and revered writers of our time 'Word-work is sublime, she thinks, because it is generative; it makes meaning that secures our difference, our human difference-the way in which we are like no other life. We die. That may be the meaning of life. But we do language. That may be the measure of our lives.' The Nobel Lecture in Literature, 1993 Spanning four decades, these essays, speeches and meditations interrogate the world around us. They are concerned with race, gender and globalisation. The sweep of American history and the current state of politics. The duty of the press and the role of the artist. Throughout A Mouth Full of Blood our search for truth, moral integrity and expertise is met by Toni Morrison with controlled anger, elegance and literary excellence. The collection is structured in three parts and these are heart-stoppingly introduced by a prayer for the dead of 9/11, a meditation on Martin Luther King and a eulogy for James Baldwin. Morrison's Nobel lecture, on the power of language, is accompanied by lectures to Amnesty International and the Newspaper Association of America. She speaks to graduating students and visitors to both the Louvre and America's Black Holocaust Museum. She revisits The Bluest Eye, Sula and Beloved; reassessing the novels that have become touchstones for generations of readers. A Mouth Full of Blood is a powerful, erudite and essential gathering of ideas that speaks to us all. 'To what do we pay greatest allegiance? Family, language group, culture, country, gender? Religion, race? And, if none of these matter, are we urbane, cosmopolitan or simply lonely? In other words, how do we decide where we belong? What convinces us that we do?' The Alexander Lecture series, 2002.
Keywords: Morrison, Toni; African American women in literature; Essays